(3GdMeGjI GdbGfhfjI GdeOfjI ddeQjV (B/ s - (3bOQj eMeO eMehOs; (3eMeO TcQi SQhQ (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2015)
(3JJfGhd GdQSGdI ehVhY GdMeGjI GdbGfhfjI GdeOfjI ddeQjV; hgj ebSeI Edi HGHjf GdChd jJfGhd GdMeGjI GdeOfjI ddeQjV CKfGA eQMdI GdaMU hGdJTNjU, hGdHGH GdKGfj jJfGhd GdMeGjI GdbGfhfjI GdeOfjI ddeQjV CKfGA GdYdGL hGdGdJRGe HGdEYdGe(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2015.s
. (3HHdjhLQGajG(B: (3UaMGJ (B-554: 588.s
Keywords: (3GdMeGjI GdeOfjI ddeQjVs; (3GdeHQQGJ GdCNdGbjI dQVGA GdeQjVs; (3eHOC GdPGJjI hMb JbQjQ GdeUjQs; (3GdJRGe GdWHjH HMeGjI GdeQjV s; (3GdNWC GdWHjs; (3GdVQQs; (3YdGbI GdSHHjI aj GdeSFhdjI GdWHjIs; (3fbd hRQY GdCYVGA Hjf GdCMjGAs; (3GdJRGe GdWHjH HGdeMGaXI Ydi CSQGQ GdegfIs; (3GdMeGjI GdeOfjI ddeQjVs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 2015